2021
DOI: 10.1016/j.jbc.2021.100566
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient availability regulates proline/alanine transporters in Trypanosoma brucei

Abstract: Trypanosoma brucei is a species of unicellular parasite that can cause severe diseases in livestock and humans, including African trypanosomiasis and Chagas disease. Adaptation to diverse environments and changes in nutritional conditions is essential for T. brucei to establish an infection when changing hosts or during invasion of different host tissues. One such adaptation is the ability of T. brucei to rapidly switch its energy metabolism from glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 125 publications
(229 reference statements)
1
22
0
Order By: Relevance
“…Closely related genes can be differentially regulated. For example, 3 members of the AAT7-B proline/alanine transporter family [ 17 ] are expressed at different times in the midgut (D3 or D15), one is biphasic (midgut D7 and proventriculus) and others show maximum expression in the proventriculus or in the salivary glands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Closely related genes can be differentially regulated. For example, 3 members of the AAT7-B proline/alanine transporter family [ 17 ] are expressed at different times in the midgut (D3 or D15), one is biphasic (midgut D7 and proventriculus) and others show maximum expression in the proventriculus or in the salivary glands.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that procyclic forms can sense and adapt to nutrient availability in culture [ 16 ]. In addition, trypanosomes deprived of glucose or amino acids react by up-regulating transcripts for amino acid transporters [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, chemotherapy is the only available option against trypanosomes as efforts to develop a vaccine have been thwarted by the international community, however, the development of trypanocidal resistance has become a realistic threat especially for persons living in endemic regions (103,145,157,158). Trypanosoma transport proteins [on the surface of the parasite (see Table 4)] are responsible for pathogen survival; and trypanocidal resistance has been associated with changes in the pathogen transportome leading to dysfunction and a loss in therapeutical potential once drugs can no longer be absorbed by the parasite (152)(153)(154)159). This justifies the need to promote further research for the discovery of novel chemotherapeutical options for the control of trypanosomiasis.…”
Section: Trypanocidal Resistancementioning
confidence: 99%
“…Protozoan parasites adapt their metabolism to the mutable environments encountered throughout their life cycle, including the hemolymph of their insect vectors (Bringaud et al, 2012). Trypanosoma brucei, the causative agent of sleeping sickness, is transmitted by tsetse flies (Glossina diptera), and both organisms can oxidize L-Pro to accomplish ATP biosynthesis (Figure 3; Michalkova et al, 2014;Mantilla et al, 2017;Smith et al, 2017;Dolezelova et al, 2020;Haindrich et al, 2021;Villafraz et al, 2021). L-Pro sustains Trypanosoma cruzi (the causative agent of Chagas disease) cell invasion and intracellular epimastigote-to-trypomastigote transition (Figure 3; Martins et al, 2009;Mantilla et al, 2015;Barison et al, 2017).…”
Section: Insect Vectors and Protozoan Parasitesmentioning
confidence: 99%